Cortical microtubule patterning in roots of Arabidopsis thaliana primary cell wall mutants reveals the bidirectional interplay with cell expansion - Panteris, Emmanuel (Plant Signal Behav, 2015)
Cell elongation requires directional deposition of cellulose microfibrils regulated by transverse cortical microtubules. Microtubules respond differentially to suppression of cell elongation along the developmental zones of Arabidopsis thaliana root apex. Cortical microtubule orientation is particularly affected in the fast elongation zone but not in the meristematic or transition zones of thanatos and pom2–4 cellulose-deficient mutants of Arabidopsis thaliana. Here, we report that a uniform phenotype is established among the primary cell wall mutants, as cortical microtubules of root epidermal cells of rsw1 and prc1 mutants exhibit the same pattern described in thanatos and pom2–4. Whether cortical microtubules assume transverse orientation or not is determined by the demand for cellulose synthesis, according to each root zone's expansion rate. It is suggested that cessation of cell expansion may provide a biophysical signal resulting in microtubule reorientation.